PENGUNGKAPAN TANGGUNG JAWAB SOSIAL PERUSAHAAN DAN TATA KELOLA PERUSAHAAN SEBAGAI PEMODERASI HUBUNGAN PENGHINDARAN PAJAK TERHADAP NILAI PERUSAHAAN (Studi Empiris pada Perusahaan Manufaktur yang terdaftar di Bursa Efek Indonesia pada tahun 2018-2020) - Nela Mukti Sari; Wahyu Meiranto (Diponegoro Journal of Accounting, 2022)
This study aims to examine how the effect of corporate governance and corporate social responsibility as moderators on tax avoidance on firm value. Corporate governance and corporate social responsibility play a role as moderate variables, each measured by the ICG (Index of Corporate Governance) and GRI Standart (Standart Global Reporting Initiative) proxy. Tax avoidance which acts as an independent variable measured by CUETR proxy (Current Effective Tax Rate). Firm value acts as the dependent variable measured using Tobin’s q.The population consist of manufacturing companies listed on the Indonesia Stock Exchange during 2018-2020. Samples are selected using purposive sampling method and acquired 228 companies during 3 years. Testing the sample using multiple linear regression with SPSS.The results of this study indicate that tax avoidance has an affect the creation of firm value. also corporate social responsibility has an influence on the relationship between tax avoidance and firm value but, for Corporate governance has no effect on the relationship between tax avoidance and firm value.